Dynamic Characteristics of Metro Trains under Rescue Conditions - Ruiming Zou; Shihui Luo; Weihua Ma; Qing Wu (Shock and Vibration)
In order to study the dynamic characteristics of metro train under rescue conditions, a detailed dynamic model with different train formations is established, taking into account the characteristics of wheel-rail contact, nonlinear characteristics of suspension components, and nonlinear hysteresis characteristics of the draft gear systems. To verify the accuracy of the simulation results, field tests are carried out and comparison is made between simulation and test results. Then, simulation analyses are conducted under the condition of AW0 rescues AW0, AW0 rescues AW3, and AW3 rescues AW3. Based on the simulation results, the longitudinal dynamic characteristics of the train under different rescue conditions are compared, and the influence of the longitudinal impulse on the dynamic performance of coupler and vehicle is analyzed. Finally, some suggestions are put forward to improve the draft gear as well as the rescue method.